Analisis peran orang tua pada pelaksanaan study from home selama masa pandemi covid-19 di sekolah dasar - Yuhanita Pratiwi Anastasia; Sri Marmoah; Hadiyah Hadiyah (Universitas Sebelas Maret, 2022)
This study discusses the role of parents in the implementation of the study from home which took place at SD Dukuhan Kerten. This study aims to determine firsthand the role of parents in implementing study from home during the covid-19 pandemic. This research uses qualitative research. This study uses a phenomenological approach with qualitative methods. Techniques in data collections are interviews, questionnaires and documentation. The subjects of this research are teachers and parents. The result showed that the role of parents in implementing study from home was very diverse and played a lot in supporting the implementation of study from home during this pandemic. There are obstacles that parents face, but parents always communicate these obstacles and find solutions with the class teacher. The positive side of online learning is that parents care more about children’s academic development and provide their best role for children. In this study shows the result of role of parents who are very involved in online learning. The role of parent is divided into 3 aspect: behavior, cognitive intellectual, and personal.